An appraisal of legislation and policy on human trafficking in Zimbabwe - Chibwe, Lydia T. (Midlands State University, 2017)
Human trafficking is considered to be modern day slavery. Zimbabwe continuously seeks to strengthen its fight against this crime, latest with the Trafficking in Persons act of 2014 and the National Action Plan against human trafficking. The thesis analysis and investigates the extent to which law is able to fight against human trafficking. This is done by analysing Zimbabwe‟s legal framework within the field of human trafficking, conducting interviews with experts, and looking at country reports, books and journals. It appears that the recent legislation and policy have got pitfalls which are hindering the effective elimination of human trafficking. This is mainly seen in the definition of human trafficking in the Trafficking in Persons act of 2014 which emphasises the transportation aspect and ignoring other important aspects such as exploitation which is essential in a definition to enable elimination of all forms of human trafficking. Hence there is need to review the available legislation and policy to avoid the inhuman practise.